2022
DOI: 10.17509/jsl.v5i1.33912
|View full text |Cite
|
Sign up to set email alerts
|

Parent Involvement in Pre-school Science Activities: What Do Parents Think About It?

Abstract: This study aimed to investigate parents' views about science and parent involvement in pre-school science activities. According to Cresswell's designs' sequential explanatory mixed-method design, the study was conducted. The participants were composed of parents of 39 children (60-72 months) who studied in two different classrooms, there were 20 children in one of the classrooms, and there were 19 children in the other classroom at a public pre-school in Ankara/Turkey in 2015-2016 school year. The Parents' Vie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…It is likely that caregivers, especially those who chose to attend FMS, already come into the program with strong beliefs regarding the importance of early math and science skills, but do not feel like they have concrete strategies to support this learning. This is consistent with previous research that has shown consistently high positive beliefs regarding the importance of mathematics for young children and the capacity for young children to learn math, but more variability in parents’ reported math practices in the home ( Missall et al, 2015 ; Şahin Çakır and Uludağ, 2022 ). In addition, caregiving beliefs are deeply engrained and culturally informed ( Sigel and McGillicuddy-De Lisi, 2002 ), and therefore harder to change.…”
Section: Discussionsupporting
confidence: 92%
“…It is likely that caregivers, especially those who chose to attend FMS, already come into the program with strong beliefs regarding the importance of early math and science skills, but do not feel like they have concrete strategies to support this learning. This is consistent with previous research that has shown consistently high positive beliefs regarding the importance of mathematics for young children and the capacity for young children to learn math, but more variability in parents’ reported math practices in the home ( Missall et al, 2015 ; Şahin Çakır and Uludağ, 2022 ). In addition, caregiving beliefs are deeply engrained and culturally informed ( Sigel and McGillicuddy-De Lisi, 2002 ), and therefore harder to change.…”
Section: Discussionsupporting
confidence: 92%
“…Although some obesity prevention efforts focus on primary schools ( 12 , 36 ), preschool environments often lack such initiatives ( 14 , 15 ). Before introducing behaviour change programmes, it is crucial to thoroughly understand the perspectives and awareness of preschool staff and parents regarding daily routines, best achieved through qualitative research ( 29 , 37 ).…”
Section: Introductionmentioning
confidence: 99%